A smart pinless ejection mechanism using dual-resonance excitation Langevin piezoelectric transducers. (30th November 2015) - Wang, Yu-Jen; Fu, Kuo-Chieh; Wang, Chun-Chieh
Abstract: This study investigated a smart pinless ejection mechanism comprising two dual-resonance excitation Langevin piezoelectric transducers (DRELPTs) for keeping the injection parts intact and protecting their top and bottom surfaces from scarring during plastic injection molding. The dimensions of each DRELPT were determined using longitudinal vibration models, and an optimization method was used to set the frequency ratio of the first to the second longitudinal mode to 1:2. This concept enables the driving of DRELPT in its two longitudinal modes consistent with the ejection direction in resonant-type smooth impact drive mechanisms. During the ejection process, DRELPT provides an ejection force, which is applied on the sidewalls of the injection parts to protect their top and bottom surfaces from scarring. Considering individual differences in the resonance frequencies of DRELPTs, a resonance frequency tracking circuit based on a phase-locked loop was designed to keep DRELPT actuating in resonance. The ejection velocity of the injection part was estimated using the kinetic models derived from the dynamic behavior of the mold cavity and injection parameters. A characteristic number S was defined to evaluate the average velocity of the injection part during ejection. Proof-of-concept experimental results of the pinless ejection mechanism are presented. The ejection time, that is, the time from triggering the composite wave to the full departure of the injection part from the mold cavity, was 72 ms.